A 15-year pheochromocytoma and paraganglioma experience in a single centre: a Singapore perspective - Yingshan Lee; Leon Yuan Rui Tan; Shaikh Abdul Kader Kamaldeen Abdul Shakoor (Singapore Medical Journal)
Introduction: Pheochromocytomas (PCC) and paragangliomas (PGL) are rare endocrine tumours. The objective of this study was to describe our experience with these two entities in a Singapore population. Methods: We identified patients with positive histopathological confirmations of PCC and PGL who were treated at a tertiary Singapore hospital between January 2000 and December 2015. The results were analysed for clinical presentations, treatment and long-term outcomes. Results: A total of 27 cases (20 PCC, 7 PGL) were identified over a 15-year period. One case of PGL developed bilateral disease on follow-up. There were 17 male and 10 female patients with a median age of 57 (range 24–77) years. A positive family history was uncommon and present in only 3.7% of patients. Uniquely, the top three presenting symptoms were abdominal discomfort, palpitations and diaphoresis. Despite adequate preoperative preparation, intraoperative haemodynamic instability occurred in 70.4% and early postoperative hypotension occurred in 11.1% of patients. After surgery, hypertension was resolved in 41.2% (7/17) and diabetes mellitus in 60% (3/5). Disease recurrence was reported in 22.2% and distant metastases in 14.8%. At the end of the follow-up period (median 35 [range 3–148] months), 70.4% were still alive. Conclusion: PCC and PGL can present with a wide range of symptoms. Intraoperative haemodynamic instability was frequent despite good preoperative preparation. Disease recurrences and metastasis occurred in up to one-fifth of the patients. Genetic screening should be offered to patients with PCC and PGL.